(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Alfalfa is one of the forage crops widely cultivated due to its adaptability on different soil and environmental conditions. This forage crop is cultivated in more than 80 countries with over 210 million tons of alfalfa hay produced. The soils of the UAE are dominantly sandy and infertile and hence show poor physical, chemical and fertility properties, suggesting frequent irrigation and replenishment nutrients based on crop requirement. Among other forages alfalfa is grown in many farms. Sustainable agriculture production system plays an important role in creating the options that enable sustainability by developing systems that are environmentally preferable, more resource-efficient, and often more cost-effective (Gupta RJ et al, 2009). Desert sandy soils are low in inherent soil fertility and due to high drainage capacity there are significant losses of nutrients and water. High temperature, water scarcity and salinity are other constraints limiting agricultural production in desert environment (Suarez et al, 2010). Salinity and drought, two very closely associated abiotic stressors, negatively affect crop productivity (Gamalero et al., 2020). Almost 20 % of the total irrigated land has been degraded due to excess soil salinity (FAO, 2020). To meet the food, fodder, biomass energy, value-added product and employment requirements of the expanding population, it is critical to developing sustainable agricultural systems under constricted conditions in these marginal lands.